Cross-sectional point prevalence survey to study the environmental contamination of nosocomial pathogens in intensive care units under real-life conditions. Issue 1 (January 2018) - Wille, I.; Mayr, A.; Kreidl, P.; Brühwasser, C.; Hinterberger, G.; Fritz, A.; Posch, W.; Fuchs, S.; Obwegeser, A.; Orth-Höller, D.; Lass-Flörl, C.
Summary: Background: In intensive care units (ICUs), inanimate surfaces and equipment may be contaminated by nosocomial pathogens, including multi-drug-resistant micro-organisms. Aims: To assess the degree of environmental contamination close to and distant from patients, and contamination of healthcare workers' (HCWs) hands with nosocomial pathogens under real-life conditions and to investigate potential transmission events. Methods: Over the course of three weeks, agar contact samples were taken close to and distant from patient areas and from HCWs' hands in eight ICUs of a tertiary care hospital in Innsbruck, Austria. Each ICU was visited once without announcement. Species identification and antimicrobial susceptibility testing were performed according to standard methods, and corresponding strains from patient, environment and hand samples were genotyped using pulsed-field gel electrophoresis. Findings: Among 523 samples, HCWs' hands were most frequently contaminated with potentially pathogenic bacteria (15.2%), followed by areas close to patients (10.9%) and areas distant from patients (9.1%). Gram-positive bacteria were identified most often (67.8%), with Enterococcus spp. being the most prevalent species (70% vancomycin sensitive and 30% vancomycin resistant) followed by Staphylococcus aureus, of which 64% were classified as meticillin-resistant Staphylococcus aureus . Molecular typing documented identical strains among patient, environment and hand isolates. Conclusion: This study found widespread contamination of the ICU environment with clinically relevant pathogens, including multi-drug-resistant micro-organisms, despite cleaning and disinfection. The bioburden might not be restricted to areas close to patients. The role of extended environmental disinfection of areas distant from patients in order to improve infection prevention needs further discussion.